Ethical Perceptions of Tax Evasion Among Non-Employee Taxpayers in Surabaya: Love of Money, Religiosity, Justice, and Culture as Moderating - Wahyudi, Nanda Syafira; Irwandi, Soni Agus (Manunggal Halim Jaya, 2025)
This study aims to examine the impact of ethical perceptions of tax evasion on non-employee taxpayers in Surabaya, with love of money, religiosity, justice, and culture as moderating variables. A quantitative research method is employed using the snowball sampling technique, involving 130 non-employee taxpayer respondents in Surabaya. Data analysis is conducted using PLS-SEM (Partial Least Squares Structural Equation Modeling) with the assistance of Smart PLS 4.0. The expected findings of this study suggest that love of money has a positive effect on ethical perceptions of tax evasion, whereas religiosity and justice have negative effects. However, when moderated by culture, love of money exhibits a negative effect, religiosity shows a positive effect, and justice has a positive effect. Nevertheless, the actual results indicate that love of money has a positive effect on ethical perceptions of tax evasion, while religiosity has no significant effect, and justice has a negative effect. When moderated by culture, love of money has no effect, religiosity demonstrates a negative effect, and justice has a positive effect. These findings highlight the complex interactions between love of money, religiosity, justice, and culture in shaping ethical perceptions of tax evasion.